Parenting and child mental health during the COVID-19 pandemic: An online study with Portuguese and British Families - Pereira, Ana Isabel (2021)
COVID-19 and the subsequent public health response created many additional stresses for families. We examined parental behaviour during the COVID-19 pandemic in two European Countries and explored the association between parents’ behaviour and children’s anxiety and quality of life. Caregivers of children and adolescents (N = 442; 86.7% mothers) between 6 and 16 years old (M = 10, SD = 2.85) participated in an online cross-sectional survey in Portugal and the United Kingdom. Results show that higher children’s anxiety and lower quality of life were associated with higher levels of unrealistic parental demands, lower parental self-care, and higher parental emotional dysregulation. Encouragement of children’s emotion expression and management of exposure to COVID-19 information was negatively associated with children’s anxiety. Promotion of routines, support of children’s emotion modulation and promotion of children’s healthy lifestyles were positively associated with children’s quality of life. The predictors differed according to country and age group. These results highlight the importance of specific parenting behaviours on children’s mental health during COVID-19. The need to moderate unrealistic demands and attend to parental self-care to reduce parental emotional dysregulation is important.